Metais pesados, atributos químicos e bioquímicos em latossolos e plantas de milho após aplicação de lodo de esgoto por dezesseis anos consecutivos - Yada, Marcela Midori [UNESP] (2014)
The addition of sewage sludge (SS) to soil have positive aspects for the improvement of agricultural soils, since they contain nutrients such as phosphorus, nitrogen, sulfur, zinc, among others, as well as providing improvements in chemical, physical and biological soil properties. The aim of this study was to evaluate the implementation effect of doses of SS for sixteen consecutive years on chemical and biochemical attributes, yield, content of macro and micronutrients on leaf diagnosis and the content of heavy metals in soil, plant and grains corn grown in Typic Eutrorthox (LVef) and Typic Haplorthox (LVd). The experiment was conducted under field conditions in Jaboticabal, SP. The experimental design was randomized blocks with four treatments and five repetitions. The treatments were: T1 = control (mineral fertilization, without application of LE), T2 = 5 t ha-1 SS, T3 = 10 t ha-1 SS and T4 = 20 t ha-1 S (dry basis). Sewage sludge caused an increase in K content in LVef and decreased in LVd. Sewage sludge increased P content in LVef and the organic matter content in LVd. The dose of 20 t ha-1 of sewage sludge, dry basis, promoted an increase in the activity of the enzyme acid phosphatase in soil LVef and arylsulfatase enzyme activity in basal respiration and metabolic quotient in soil LVd. The application of 10 and 20 t ha-1 SS, dry basis, increased the Cu content in the soil LVef and Cu, Ni, Pb and Zn in the soil LVd, however, without exceeding the values of prevention established by legislation Brazilian. The content of Cd, Ni, Pb and Zn in plants of corn grown in LVef and LVd increased with application of sewage sludge, but without difference between doses of 5, 10 and 20 t ha-1. The levels of the metals As, Ba, Cd, Cr, Hg, Mo and Pb in the grains of corn remained below the limits for human consumption. Only the Ni present effect of doses of LE applied to two soils. There was no significant difference between treatments ...